Plasma proteome profiles treatment efficacy of incretin dual agonism in diet‐induced obese female and male mice. Issue 1 (5th November 2020) - Sachs, Stephan; Niu, Lili; Geyer, Philipp; Jall, Sigrid; Kleinert, Maximilian; Feuchtinger, Annette; Stemmer, Kerstin; Brielmeier, Markus; Finan, Brian; DiMarchi, Richard D.; Tschöp, Matthias H.; Wewer Albrechtsen, Nicolai; et al.
Abstract: Aims: Unimolecular peptides targeting the receptors for glucagon‐like peptide‐1 (GLP‐1) and glucose‐dependent insulinotropic polypeptide (GIP) (GLP‐1/GIP co‐agonist) have been shown to outperform each single peptide in the treatment of obesity and cardiometabolic disease in preclinical and clinical trials. By combining physiological treatment endpoints with plasma proteomic profiling (PPP), we aimed to identify biomarkers to advance non‐invasive metabolic monitoring of compound treatment success and exploration of ulterior treatment effects on an individual basis. Materials and methods: We performed metabolic phenotyping along with PPP in body weight‐matched male and female diet‐induced obese (DIO) mice treated for 21 days with phosphate‐buffered saline, single GIP and GLP‐1 mono‐agonists, or a GLP‐1/GIP co‐agonist. Results: GLP‐1R/GIPR co‐agonism improved obesity, glucose intolerance, non‐alcoholic fatty liver disease (NAFLD) and dyslipidaemia with superior efficacy in both male and female mice compared with mono‐agonist treatments. PPP revealed broader changes of plasma proteins after GLP‐1/GIP co‐agonist compared with mono‐agonist treatments in both sexes, including established and potential novel biomarkers for systemic inflammation, NAFLD and atherosclerosis. Subtle sex‐specific differences have been observed in metabolic phenotyping and PPP. Conclusions: We herein show that a recently developed unimolecular GLP‐1/GIP co‐agonist is more efficient in improving metabolic disease than either mono‐agonist in both sexes. PPP led to the identification of a sex‐independent protein panel with the potential to monitor non‐invasively the treatment efficacies on metabolic function of this clinically advancing GLP‐1/GIP co‐agonist.